Delayed uterine rupture occurred 4 weeks after cesarean section following sexual intercourse: A case report and literature review - Hsing-Fen Tsai; Hsiang-Lin Song; Wen-Chung Chen; Chia-Ming Chang; Chiung-Hsin Chang; I-Wen Lee (Elsevier, 2013)
Objective: Spontaneous delayed uterine rupture is life-threatening and extremely rare following sexual intercourse in postpartum. Here, we present a case of delayed uterine rupture that occurred 4 weeks after cesarean section following intercourse. Case report: A 31-year-old postpartum woman, gravida 4, para 1, abortion 3, underwent a cesarean section for prolonged labor. She was transferred to our hospital in shock status with brisk vaginal bleeding following intercourse 4 weeks after delivery. An emergency subtotal hysterectomy was performed to stop the bleeding. The pathology confirmed tissue necrosis and suture granuloma at the previous surgical wound. Conclusion: The presented case demonstrated that delayed uterine rupture may occur even 4 weeks after delivery following intercourse, without any obvious abdominal pain or infection signs, which deserved the attention of obstetricians.